Abnormality of the N-Terminal Portion of von Willebrand Factor in Type IIA and IIC von Willebrand Disease - Takahashi, Y; Kalafatis, M; Girma, J P; Meyer, D (Thrombosis and Haemostasis, 1988)
We have established a new analytical method which allows the characterization of von Willebrand factor (vWF) degradation fragments in minute amounts (10 μ1) of plasma, without the need for immunopurification of vWF. Plasma vWF was hydrolysed by S aureus V-8 protease (V-8 protease) and the cleaved fragments separated by SDS-agarose gel electrophoresis followed by staining with 125I-labeled polyclonal or monoclonal antibodies against vWF and autoradiography. Quantification of the amount of each product was estimated by counting the incorporated radioactivity following excision. V-8 protease limitedly hydrolysed vWF in normal as well as type I von Willebrand disease (vWD) plasma and produced two distinct fragments with identical electrophoretic and antigenic characteristics to those produced from purified vWF, i.e. a C-terminal SpII and a series of N-terminal Spill fragments (SpIIIa, b and c). The method was applied to further characterize the molecular abnormalities of vWF in eighteen patients with type II vWD. In seven individuals with type IIA and five patients with type IIC, Spill appeared significantly modified as compared to normal. In type IIA, there was a marked decrease or absence of SpIIIa and an increase of SpIIIb and c. In type IIC, SpIIIb was lacking. In three patients with type IIB and in three patients with type IID, there was no significant modification of Spill. In all cases, SpII was apparently not modified. In conclusion, the molecular abnormality of vWF in type IIA and IIC vWD appears to reside in Spill, the N-terminal portion of the vWF-subunit (residues 1 to 1,365).
Keywords: von Willebrand factor (vWF); von Willebrand disease (vWD); S aureus V8 protease (V8-protease)